Effects Of Feeding Milk Replacer On Selected Haemato- Biochemical Profile In Yak (Bos Grunniens) Calves. - Morang, M.; Sarma, N. K.; Chakravarty , P.; Sarma , K. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
An experiment was conducted to find out the effect of feeding milk and milk replacer on selected haemato-biochemical constituents of Yak calves up to 3 months of age. The calves were subjected to three feeding regimes viz. natural suckling (T1), milk replacer (T2) and bottle whole milk feeding (T3). No significant difference in the levels of blood serum haemoglobin, glucose, cholesterol, calcium, phosphorus, magnesium and albumin were observed among the three treatments indicate that feeding milk replacer has no effect on these blood components.